Semen quality of 4480 young cancer and systemic disease patients: baseline data and clinical considerations. Issue 1 (December 2016) - Auger, Jacques; Sermondade, Nathalie; Eustache, Florence
Abstract Background Except for testicular cancer and Hodgkin's disease, baseline data on semen quality in case of cancers as well as systemic pathologies of the young adult are scarce or based on low sample size. Methods Semen quality in patients having testicular cancer (TGCT, n  = 2315), Hodgkin's disease (HD, n  = 1175), non-Hodgkin's lymphoma (NHL, n  = 439), leukemia (L, n  = 360), sarcoma (S, n  = 208), brain tumour (BT, n  = 40), Behcet's disease (Behcet's, n  = 68) or multiple sclerosis (MS, n  = 73) was studied and compared to that of 1448 fertile men candidates for sperm donation (CSD) and 208 partners of pregnant women (PPW). All samples were studied following the same methodology in a single laboratory. Post freezing and thawing semen characteristics were also studied. Results The percentage of normozoospermic men was only 37 % for L patients and lower than 60 % for TGCT, NHL, S and BT. The level of sperm production was differently decreased according to pathologies, the median total sperm count in TC and L patients being four times lower (p  < 0.01 when compared to CSD and PPW). The lowest percentage of progressively motile spermatozoa was found for L and BT patients (both, p  < 0.01 compared to CSD and PPW). The percentage of morphologically normal spermatozoa was also reduced in cancer patients, especially in BT patients. Progressive motility after thawing in patients was about half that observed among candidates for sperm donation. In almost half of the semen of patients with testicular cancer or leukemia, the total number of motile spermatozoa per straw was less than 0.5 × 106 compared to 4.3 × 106 in CSD. Conclusions The present data confirm on large series the deleterious impact of various cancers of the young adult on semen quality, establishing thus baseline data for future studies. Owing to the post-thaw quality of the frozen straws, future fertility projects for the majority of the patients studied (in case there is no post-treatment recovery of spermatogenesis) should necessitate an ICSI to provide the best chance of paternity whatever the fertility check-up in the female partner. French language Abstract Contexte En dehors du cancer du testicule et de la maladie de Hodgkin, les données de la littérature sur la qualité du sperme dans le cas de cancers et de maladies systémiques du jeune adulte sont rares et le plus souvent basées sur de faibles effectifs. Méthodes La qualité spermatique de patients ayant un cancer du testicule (TGCT, n  = 2 315), une maladie de Hodgkin (HD, n  = 1175), un lymphome non Hodgkinien (LNH, n  = 439), une leucémie (L, n  = 360), un sarcome (S, n  = 208), une tumeur cérébrale (BT, n  = 40), une maladie de Behcet (Behcet, n  = 68) ou une sclérose en plaque (MS, n  = 73) a été étudiée et comparée à celle de 1448 hommes féconds candidats au don de spermatozoïdes (CSD) et 208 partenaires de femmes enceintes (PPW), utilisant la même méthodologie dans un seul laboratoire. Les caractéristiques du sperme après dégel ont également été analysées. Résultats Le pourcentage de spermes normozoospermiques était seulement de 37 % chez les patients L, et < 60 % pour les patients TGCT, NHL, S et BT. La production spermatique était diminuée dans la plupart des pathologies, le nombre total spermatozoïdes par éjaculat des patients TC et L étant 4 fois plus faible (p <0, 01 par rapport aux hommes féconds). Le plus faible pourcentage de spermatozoïdes mobiles a été trouvé pour les patients L et BT (p <0, 01 par rapport aux hommes féconds). Une diminution du pourcentage de spermatozoïdes normaux a aussi été observée chez les patients cancéreux, particulièrement pour les patients BT. La motilité progressive après décongélation des patients était diminuée de moitié par rapport aux candidats pour le don de sperme. La médiane du nombre total de spermatozoïdes mobiles par paillette était inférieure à 0, 5 × 106 pour TGCT et L contre 4, 3 × 106 pour les candidats au don. Conclusion Les données présentées obtenues sur de grandes séries rarement publiées constituent des données de référence pour de futures études. Dans le cas d'une utilisation de paillettes en AMP, l'ICSI sera nécessaire dans la majorité des cas.